2020
DOI: 10.1007/s43032-020-00357-6
|View full text |Cite
|
Sign up to set email alerts
|

Histologic Analysis of Testes from Prepubertal Patients Treated with Chemotherapy Associates Impaired Germ Cell Counts with Cumulative Doses of Cyclophosphamide, Ifosfamide, Cytarabine, and Asparaginase

Abstract: Cryopreservation of immature testicular tissue is an experimental strategy for the preservation of fertility in prepubertal boys that will be subjected to a gonadotoxic onset, as is the case of oncologic patients. Therefore, the objective of this study was to assess the impact of chemotherapeutic treatments on the testicular histologic phenotype in prepubertal patients. A total of 56 testicular tissue samples from pediatric patients between 0 and 16 years old ( 28with at least one previous chemotherapeutic ons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 41 publications
3
14
1
Order By: Relevance
“…However, as chemotherapeutic agents are mostly administered in combination, it is difficult to assess the individual risk per agent ( 58 , 67 , 69 ). Moreover, most results are extrapolated from animal or adult studies, making additional research necessary to verify these risk classifications/dosages in children ( 67 , 68 , 75 , 76 , 191 ). Therefore, studies with human-relevant experimental systems such as human organoids ( 18 ) or human organotypic culture combined with xenografting ( 192 ), could be helpful tools to characterize the exact effects of a chemotherapeutic agent on prepubertal testicular tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as chemotherapeutic agents are mostly administered in combination, it is difficult to assess the individual risk per agent ( 58 , 67 , 69 ). Moreover, most results are extrapolated from animal or adult studies, making additional research necessary to verify these risk classifications/dosages in children ( 67 , 68 , 75 , 76 , 191 ). Therefore, studies with human-relevant experimental systems such as human organoids ( 18 ) or human organotypic culture combined with xenografting ( 192 ), could be helpful tools to characterize the exact effects of a chemotherapeutic agent on prepubertal testicular tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Besides this, it remains a challenge to identify the individual risk per molecule, as these are usually administered in combinations ( 58 , 67 , 69 , 74 ). Moreover, most data either come from animal experiments or studies performed in adult men, which makes it difficult to extrapolate these risks to young patients ( 67 , 75 , 76 ). As the exact risk classifications/dosages for children remain unclear, further research on prepubertal exposure is warranted together with regular updates of this classification ( 67 , 68 ).…”
Section: Malignant Diseasesmentioning
confidence: 99%
“…In Europe, carboPEI 7,8 is delivered with large volumes of intravenous hydration, can exacerbate pre‐existing DI, particularly where no thirst mechanism is present, and is associated with prolonged inpatient admissions 20 . Such chemotherapy schedules are also associated with short‐ 8 and long‐term 11–13,16 toxicities and, moreover, require central venous access devices for delivery, with associated infection and thrombosis risk 14,15 . A further UK intracranial germinoma case, in addition to the two formally described here, received two vinblastine doses to complete induction as a “bridge” to radiotherapy with stable radiological appearances; this patient developed ifosfamide encephalopathy 23 during standard‐of‐care carboPEI chemotherapy and experienced a fall and subdural hematoma.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the challenges of managing DI, carboPEI chemotherapy is associated with short‐term toxicities of myelosuppression, vomiting and/or diarrhoea, electrolyte disturbances, which may lead to seizures, renal impairment and elevation of liver enzymes 8 . Long‐term sequelae of these drugs include ototoxicity from cisplatin 11 and reduced fertility from alkylating agents (ifosfamide) 12,13 . Current chemotherapy regimens also require the use of indwelling central venous access devices, which are associated with increased risk of infection 14 and thrombosis 15 and which may affect quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of prepubertal patients have received chemotherapy regimens, considered to be at low gonadotoxic risk, before the preservation of their testicular tissues 22 , 23 . Some studies have demonstrated that the administration of chemotherapy before puberty led to a decrease in the number of spermatogonia, especially when alkylating agents were included in the therapy regimen 24 26 . The depletion of the spermatogonial stem cell (SSC) pool could compromise the chances of fertility restoration.…”
Section: Introductionmentioning
confidence: 99%